Indigeneity on the Oceanic Stage : Intimations of the Local in a Globalised World - Maufort, Marc,; O'Donnell, David, (Cross/Cultures ;, 2025)
This volume examines how Indigenous theatre and performance from Oceania has responded to the intensification of globalisation from the turn of the 20th to the 21st centuries. It foregrounds a relational approach to the study of Indigenous texts, thus echoing what scholars such as Tui Nicola Clery have described as the stance of a "Multi-Perspective Culturally Sensitive Researcher." To this end, it proposes a fluid vision of Oceania characterized by heterogeneity and cultural diversity calling to mind Epeli Hau'ofa's notion of "a sea of islands." Taking its cue from the theories of Deleuze and Guattari, the volume offers a rhizomatic, non-hierarchical approach to the study of the various shapes of Indigeneity in Oceania. It covers Indigenous performance from Aotearoa/New Zealand, Hawai'i, Samoa, Rapa Nui/Easter Island, Australia and the Torres Strait Islands. Each chapter uses vivid case histories to explore a myriad of innovative strategies responding to the interplay between the local and the global in contemporary Indigenous performance. As it places different Indigenous cultures from Oceania in conversation, this critical anthology gestures towards an "imparative" model of comparative poetics, favouring negotiation of cultural difference and urging scholars to engage dialogically with non-European artistic forms of expression.